9-2x+3=x-6

Simple and best practice solution for 9-2x+3=x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-2x+3=x-6 equation:


Simplifying
9 + -2x + 3 = x + -6

Reorder the terms:
9 + 3 + -2x = x + -6

Combine like terms: 9 + 3 = 12
12 + -2x = x + -6

Reorder the terms:
12 + -2x = -6 + x

Solving
12 + -2x = -6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + -2x + -1x = -6 + x + -1x

Combine like terms: -2x + -1x = -3x
12 + -3x = -6 + x + -1x

Combine like terms: x + -1x = 0
12 + -3x = -6 + 0
12 + -3x = -6

Add '-12' to each side of the equation.
12 + -12 + -3x = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -3x = -6 + -12
-3x = -6 + -12

Combine like terms: -6 + -12 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| 4=-3x+47 | | =5(2x+1)-3(2x-3) | | x^3+2x^2+7x+3ifx=10 | | -17-11z=104 | | 6x-12=-2x | | 60=4w+12 | | -2n=6-n | | 4(y+3)+8=80 | | 4(7x-4)+3(13-4x)-3(5x+5)=-3 | | 24k+15= | | 7(x+6)=6(x-3) | | 3x-11=10x+12 | | x-(x*0.25)-(x*0.3399)=50000 | | 0=16t^2-300t+2000 | | 21d^2-7d=O | | 6x+4y-2x+5y-5x= | | 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 |

Equations solver categories